Computer vision syndrome among university students during the corona virus pandemic - Alsaad, Mouna; Shehadeh, Amin; Meqbil, Jehad; Al Odat, Israa; Jamous, Sara; Khawaldeh, Taima; Al Khreisha, Hadeel; Alkubaisi, Fatima Abdulsattar; Odat, Baraa Ayed (Intelektual Pustaka Media Utama, 2023)
Computer vision syndrome (CVS) is a group of eye and visual problems related to computer use and it is associated with near work. The aim is to determine CVS prevalence, major complaints and main preventive practices among the University of Jordan students after the COVID-19 pandemic era. We conducted a cross-sectional descriptive study using an online pre-tested structured questionnaire. Each participant completed the questionnaire before and after the COVID-19 pandemic and the results were compared. A total of 634 students were included in the study. A high prevalence of CVS was observed after the COVID 19 era. The most significant risk factors for the presence of CVS before and after the pandemic were daily hours use of E-device for studying (p<0.001) and the use of glasses or contact lens (p<0.05). Brightness adjustment, keeping sufficient distance away from the device, taking breaks, increasing the screen font size and using eye drops were the most significant preventive measures taken by students before and after the pandemic (p<0.05). It is a necessity to raise awareness among students regarding computer related health problems and preventive measures need to be adopted to address the risk factors.